2020
DOI: 10.3390/ma13194359
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Biological Characterization of Silver-Doped Anodic Oxide Coating on Titanium

Abstract: Despite the high biocompatibility and clinical effectiveness of Ti-based implants, surface functionalization (with complex osteointegrative/antibacterial strategies) is still required. To enhance the dental implant surface and to provide additional osteoinductive and antibacterial properties, plasma electrolytic oxidation of a pure Ti was performed using a nitrilotriacetic acid (NTA)-based Ag nanoparticles (AgNP)-loaded calcium–phosphate solution. Chemical and structural properties of the surface-modified tita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 49 publications
(54 reference statements)
1
10
0
Order By: Relevance
“…The Cur-AgNPs also showed low cytotoxicity. These results stand alongside previous work suggesting that AgNPs mediate stimulation of transcriptional changes towards improved skin appearance 40 , 41 . This reflects the function of fibroblasts in mediating the secretion of extracellular matrix facilitating collagen production which corresponds to the re-epithelialization phase of wound healing 42 .…”
Section: Resultssupporting
confidence: 88%
“…The Cur-AgNPs also showed low cytotoxicity. These results stand alongside previous work suggesting that AgNPs mediate stimulation of transcriptional changes towards improved skin appearance 40 , 41 . This reflects the function of fibroblasts in mediating the secretion of extracellular matrix facilitating collagen production which corresponds to the re-epithelialization phase of wound healing 42 .…”
Section: Resultssupporting
confidence: 88%
“…All samples were rinsed with distilled water and ultrasonically cleaned in deionized water and 2-propanol for 5 minutes prior to PEO treatment. As the electrolyte, a suspension of Ag nanoparticles (180 mg L -1 ) in a solution containing an organic chelating agent (nitrilotriacetic acid), KH2PO4, and Ca(OH)2 was used [51].As the cathode, a titanium mesh was used, and as the anode, the treated scaffold sample was used. To remove any unattached AgNPs, the treated samples were ultrasonically cleaned after the PEO process in 2-propanol for 5 minutes and rinsed with deionized water.…”
Section: Plasma Electrolytic Oxidation (Peo) Of Scaffoldsmentioning
confidence: 99%
“…Ag nanoparticles were obtained from Nanopure, Poland. The characterization of the AgNPs was described in [51].…”
Section: Plasma Electrolytic Oxidation (Peo) Of Scaffoldsmentioning
confidence: 99%
“…These dents can be flexible, giving ChAs 06038-2 highly reactive and versatile binding possibilities not only to form complexes with metal ions, but also to bind with metal oxide surface [18]. We recently showed that the NTA can improve deposition of Ag nanoparticles into the PEO surface layers on titanium implants to render them the bacteriostatic properties [10]. Here we continued to investigate the positive effects of addition of the NTA into the PEO bath electrolyte containing potassium phosphate and calcium formate.…”
Section: Introductionmentioning
confidence: 99%
“…The PEO surfaces were made suitable for successful bone integration [6] and to support proliferation of mesenchymal stem cells [7]. On the other hand, the PEO layers were rendered bacteriostatic properties via incorporation of Ag and Cu nanoparticles [8,9,10]. The surface morphology of the PEO layers can also be modified in order to achieve the desired structure which could improve cellular adhesion and viability [11].…”
Section: Introductionmentioning
confidence: 99%